Enhancing faculty members’ technology-enhanced teaching practices through leadership - Zhang, Yanle; Chen, Dandan (Frontiers in Education, 2025)
There is an emerging consensus that technology-integrated practices are an effective approach to teaching and learning in higher education. However, despite the substantial investment in technology as an instrument to help teachers and students in an effective manner for higher education, the faculty members are not maximizing the potential of these resources. Through interviews with eight faculty members and three deans from second-tier colleges in Zhejiang, the study explores key factors influencing technology integration and effective leadership strategies for enhancing faculty members’ technology-enhanced teaching practices within second-tier colleges of Chinese higher education institutions. Findings reveal that faculty members’ technology integration is shaped by intrinsic factors, such as personal goals and willingness to innovate, and extrinsic factors, including access to resources, funding, time, organizational culture, and leadership support. Specific leadership strategies emerged as critical, including setting clear technology goals, providing professional development opportunities, fostering a collaborative culture, and offering incentives such as funding and recognition for innovation. Based on these findings, the study proposes a leadership impact model on technology integration, emphasizing the importance of tailored approaches that address both institutional and individual barriers. Policy recommendations include allocating dedicated funding for technology initiatives, ensuring equitable access to resources, and promoting inter-institutional collaboration to leverage expertise. The findings demonstrate the efficacy of leadership strategies for technology integration in aligning with and extending the Technology Acceptance Model (TAM) and the Path-Goal Theory within the unique context of Chinese higher education.